2017
DOI: 10.1002/admi.201700970
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Thin Films for Fluid Manipulation

Abstract: The ability to control nanoflows is critical to design and fabricate ever more versatile nanosystems. Scientists are currently interested in finding ways to handle fluid dynamics inside nanoporous networks, not only to increase our knowledge of fluidic behavior but also to develop novel nanodevices that have potential utility in applications ranging from diagnostics to the production of high‐value chemicals. Here, we demonstrate how fluid motion can be manipulated by controlling the coexisting infiltration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…We next achieved a high degree of control over the resultant drop evaporation rate and vividly observed peculiar behaviors by varying the value of A w . Based on our previous works that showed that the wetted annulus can be easily tuned by salt concentration and temperature changes ( A w increases with an increase in the salt concentration or a decrease in the temperature, and vice versa , as it is further explained below), we designed two exemplary systems in which variations in salt concentration or temperature permit the distinctive behaviors in the droplet evaporation on nanoporous surfaces to be revealed. We then performed the drop evaporation experiments, similar to the one presented in Figure , but using aqueous solutions with different sodium chloride concentrations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We next achieved a high degree of control over the resultant drop evaporation rate and vividly observed peculiar behaviors by varying the value of A w . Based on our previous works that showed that the wetted annulus can be easily tuned by salt concentration and temperature changes ( A w increases with an increase in the salt concentration or a decrease in the temperature, and vice versa , as it is further explained below), we designed two exemplary systems in which variations in salt concentration or temperature permit the distinctive behaviors in the droplet evaporation on nanoporous surfaces to be revealed. We then performed the drop evaporation experiments, similar to the one presented in Figure , but using aqueous solutions with different sodium chloride concentrations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The response of the system to different temperatures was studied through experiments similar to those presented in Figure 3, but setting constant temperatures by using a Peltier cell brought into contact to the lower substrate. [27] The results are summarized in Figure 5, where the expected trend of evaporation rate with temperature is observed. In particular, the evaporation rate in the N-W systems slowly increases with temperatures, in comparison to the D-W system.…”
Section: The Effect Of Substrate Temperaturementioning
confidence: 80%
“…At this point, it is worth emphasizing that the film becomes wetted without a bulk fluidic connection with the droplet, in contrast to previous setups where MTF were infiltrated from liquid reservoirs. 10…”
Section: Resultsmentioning
confidence: 99%
“…7,8 Liquid from these sessile droplets infiltrates the porous matrix via capillary imbibition and builds a defined wetted region with a fluid front that advances in the mesoporous film. 7 For instance, nanofluidic platforms based on MTF have been used to implement localized chemical reactions, 9 for nanoflow manipulation, 10 as a fluid sensor, 11 and, notably, as an electrical current nanogenerator. 12…”
Section: Introductionmentioning
confidence: 99%